แนวทางการพัฒนาการบริหารความเสี่ยงของโรงเรียนโยธินบูรณะตามแนวคิดโรงเรียนมาตรฐานสากล - เวียงคำ, สรนันท์; ไตรวิจิตรคุณ, ดวงกมล (An Online Journal of Education, 2018)
This research paper is a descriptive research. The purposes of this study is to find the risk factors and the solutions to manage those factors of Yothinburana school regarding world class standard school ideology.. observers Included a school director, 3 deputy school directors, 9 headmen from each subject’s department, 45 representative teachers from each group of subjects, in total 58 observers. Research’s tool is a five – rating-scaled questionnaire and focus group. Data were analyzed by frequent, percentage, average and stand deviation. There are research results as follows: The risk management of the world class standard school of Yothinburana school. This research found that students have the potential. However, there is a very high level of risk. Students are not able to communicate effectively in English and students cannot use any other foreign languages to communicate effectively. The management of teaching and learning regarding international standards Indicates that there is a high level of risk about ability of teachers in using English under criteria and the teacher has to use limited numbers of high quality standard books, textbooks and media. The last is management with quality system. There is a very high level of risk in this issue. Especially innovative teaching management found that there is a lacking of good knowledge management systems. The development guidelines for risk management of Yothinburana School according to international school standards are: 1. The students have the potential. The risk management approach should be used to reduce risk and control risk by identifying risk prevention measures such as content updates, student development guides and learning resources. 2. Instructional management comparable to international standards. Risk management should be implemented by mitigating risks and controlling risks associated with the transfer of risks, such as teacher development, the provision of foreign teachers who need to be native speakers, quality books and media. According to international standards The standard of performance of school personnel is set. 3. Management with quality system. The risk management approach should be used to reduce risk and control risk by implementing measures to prevent risks, for example teacher development, by providing seminars, incentives and incentives for teachers.